PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Erliana, Mutia; Febriandi, Riduan; Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Make a Match model on the learning outcomes of fifth-grade students of SD Negeri 28 Lubuk Linggau. This study has two sample groups, namely the experimental class given the Make a Match model treatment and the control class will be given treatment with conventional learning or lectures. The study population is the fifth grade of SD Negeri 28 Lubuk Linggauas many as 2 classes consisting of class A, namely 24 students and class B consisting of 24 students. The reresearch method is quasi-experimental design with the control group pretest-p-posttest category. The data collection technique uses a multiple choice test of 15 questions. Based on the results of the study, it shows that there is a significant influence on the learning outcomes of the sciences as evidenced by using the t-test, t count 3.27 can be obtained with dk = 46. So the t table value is 1.678. It is concluded that there is a significant influence of the Make a Match model on the learning outcomes of fifth-grade students of SD Negeri 28 Lubuk Linggau to achieve the KKTP